Pengaruh Kompetensi Terhadap Kinerja Pegawai Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Tasikmalaya - Firmansyah, Ade Dony (Jurnal Ilmu Administrasi Negara (JUAN), 2020)
In order to answer strategic issues and achieve the vision and mission of the Human Resources Development and Human Resources Agency of Tasikmalaya City Agency requires high employee performance. Employee performance problems that are still not optimal can be seen from the reliability of work is still low, employees do not complete the tasks given on time, employees do not work according to the set working hours, employees do not cooperate with colleagues. These performance problems require increased competence from employees of the Tasikmalaya City Human Resources and Human Resources Development Agency to be in line with the vision and mission to be achieved This study aims to determine the effect of competition on employee performance in the Human Resources Development and Human Resources Agency of Tasikmalaya City, with the research method used explanatory research. The respondents of this study are employees at the Human Resources Development and Human Resources Agency of the City of Tasikmalaya. Data analysis technique is done through regression test. Based on the results of the study showed that there was a strong influence between competence on the performance of employees in the Human Resources and Human Resources Development Agency in Tasikmalaya City. The conclusion of this study is that all factors consisting of competencies are achievement and action oriented, helping and serving others, the ability to influence and create impact, managerial ability, cognitive ability and personal effectiveness have an influence on employee performance in the Personnel Agency and Resource Development Human City of Tasikmalaya.